Firearm Injuries Cause Disproportionate Mortality in Pediatric Traumatic Brain Injury. (1st September 2019) - Gupta, Saksham; Hauser, Blake M; Zaki, Mark M; Cote, David J; Izzy, Saef; Smith, Timothy R; Khawaja, Ayaz M
Abstract: INTRODUCTION: Traumatic brain injury is a major cause of mortality and long-term morbidity in the pediatric population. Given renewed legislative efforts aimed at reducing firearm violence and harm, we sought to investigate the impact of firearms on mortality associated with TBI. METHODS: A multicentric, retrospective cohort analysis of pediatric patients with TBI was conducted using the National Trauma Data Bank from 2011 to 2014. The primary outcome was mortality within the hospital; the primary exposure was firearm-related vs. non-firearm-related TBI. RESULTS: Pediatric patients with firearm-related TBI (n = 1, 417; median [IQR] age 16 [13-17]) and non-firearm-related TBI (n = 123, 740; median [IQR] age 11 [5-15]) were included. Firearm injuries included intentional harm by others (56%), suicide attempts (29%), and accidental harm by others (15%). The majority of African-American firearm-related TBIs presented after assault (79.6%), whereas the majority of White cases presented after suicide attempts (55.6%). Firearm-related cases presented with an average adjusted GCS 3.4 points lower than non-firearm-related TBI. 50.0% of firearm-related cases died while in the hospital compared to 2.8% of non-firearm cases. The firearm injury type with the highest rate of mortality was self-harm/suicide attempts (69.8%). Relative to non-firearm cases, firearm injuries were identified to be an independent predictor of in-hospital mortality (OR 8.3; 95% CI 7.1-9.7); firearm suicide attempt injuries were the most lethal (OR 13.0; 95% CI 9.9-17.0). Although firearm injuries comprised only 1.1% of all TBIs, they were the cause of injury in 16.7% of all deaths. Male sex, Black race, and public and self-pay insurance predicted firearm injuries. CONCLUSION: Firearm-related injuries are associated with disproportionately high mortality in pediatric TBI, especially in suicide attempts. African-Americans are at disproportionately high risk of firearm assault relative to Whites. Public health and policy interventions could target youth firearm injuries and potentially prevent a significant portion of TBI deaths.